Perancangan Sistem Informasi Sekolah SD Negeri 4 Kerta Payangan Menggunakan Metode Design Thinkin - Murniati, Ni Luh Made; Swastika, I Putu Agus; Dewi, Putri Anugrah Cahya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
School information systems are one of the most important needs in educational institutions. Building a school information system is the right step to help provide more relevant information and also in processing data in schools into useful information. However, there are some schools that have not implemented it such as SD Negeri 4 Kerta, In providing conventional information that is done manually where all data or documents are stored in hardcopy form, as well as in processing data such as school profile information, academic and school finances. The purpose of this study is to determine the design of the school information system user interface to be a solution to these problems. This research uses the Design Thinking method implemented to design a website-based school information system for SD Negeri 4 Kerta. The user interface design of the school information system is built in the form of a prototype using the figma application. This study used interview methods and literature studies in collecting data and related information. And the result of designing the user interface of the SD Negeri 4 Kerta school information system is to design a website to provide school information and to process school data and process the financial section.